Andreev-reflection spectroscopy of ferromagnets: the impact of Fermi surface mismatch - Tuuli, Elina; Gloos, Kurt (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
We have investigated point contacts between a superconductor (Nb, AuIn2) and a normal metal (ferromagnetic Co, nonmagnetic Cu). The observed Andreev-reflection spectra were analyzed using the modified BTK theory including spin polarization effects. This resulted in a polarization of Co that agrees with observations by others, but lifetime effects describe the spectra equally well. On the other hand, the spectra with nonmagnetic Cu can be well described using the spin-polarization model. The ambiguity between polarization and lifetime interpretation poses a dilemma which can be resolved by considering the normal reflection at those interfaces due to Fermi surface mismatch. Our data suggest that Andreev reflection at Nb–Co contacts does deliver the true magnetic polarization of Co only when lifetime effects and the mentioned intrinsic normal reflection are included.